Sleep Characteristics of the Staff Working in a Pediatric Intensive Care Unit Based on a Survey - Puerta, Yolanda; García, Mirian; Heras, Elena; López-Herce, Jesús; Fernández, Sarah N.; Mencía, Santiago, Sleep Study Group; Corchado, Alba M.; Obeso, Rosa M.; García-Moreno, Ana B.; Jiménez, Bryan; Gil, Esther; et al. (Frontiers in Pediatrics, 2017)
The objective is to evaluate the sleep characteristics of the staff working in a pediatric intensive care unit (PICU). They were asked to complete an anonymous survey concerning the characteristics and quality of their sleep, as well as the impact of sleep disturbances on their work and social life, assessed by FOSQ-10 questionnaire. The response rate was 84.6% (85% females): 17% were doctors, 57% nurses, 23% nursing assistants and 3% porters. 83.8 % of them worked on fix shifts and 16.2% did 24-hour shifts. 39.8% of workers considered they had a good sleep quality and 39.8% considered it to be poor or bad. The score was good in 18.2% of the staff and bad in 81.8%. Night shift workers showed significantly worse sleep quality on both the objective and subjective evaluation. There was a weak concordance (kappa 0.267; p= 0.004) between the perceived quality of sleep and the FOSQ-10 evaluation. Sleep disorders affected their emotional state (30.2% of workers) and relationships or social life (22.6%). In conclusion, this study finds that a high percentage of health professionals from PICU suffer from sleep disorders which affect their personal and social life. This negative impact is significantly higher in night shift workers. Many health workers are not aware of their bad sleep quality.